2017
DOI: 10.3390/dj5020019
|View full text |Cite
|
Sign up to set email alerts
|

Dental Wear: Attrition, Erosion, and Abrasion—A Palaeo-Odontological Approach

Abstract: This paper reviews the surface ablation of early hominin teeth by attrition, abrasion, and erosive dental wear. The occurrence of these lesions is explored in a sample of South African fossil australopithecine dentitions revealing excessive wear. Interpretation of the nature of the dietary components causing such wear in the absence of carious erosion provides insight into the ecology of the Plio-pleistocene epoch (1–2 million years ago). Fossil teeth inform much of the living past by their retained evidence a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 10 publications
(10 reference statements)
1
22
0
3
Order By: Relevance
“…Age-related lip thinning and dental wear is well recognised. 4,8,16,17,[30][31][32] Similar to Schmidlin et al's study, 17 this study observed a similar decrease in lip heights for both black and white individuals. Thus, even though both groups experienced lip thinning with age, black individuals maintained considerably thicker lip heights compared to white individuals.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Age-related lip thinning and dental wear is well recognised. 4,8,16,17,[30][31][32] Similar to Schmidlin et al's study, 17 this study observed a similar decrease in lip heights for both black and white individuals. Thus, even though both groups experienced lip thinning with age, black individuals maintained considerably thicker lip heights compared to white individuals.…”
Section: Discussionsupporting
confidence: 76%
“…8,30,31 The observed dental wear is attributed to three factors: attrition, abrasion and erosion. 30,32 Attrition is caused by mastication or grinding between opposing teeth. The effect of attrition can be exacerbated in those who eat a particularly fibrous diet, or habitually clench and grind their teeth.…”
Section: Discussionmentioning
confidence: 99%
“…There are different causes determining the enamel consumption [15] and they are generally addressed as wear phenomena.…”
Section: Wear Typesmentioning
confidence: 99%
“…The mechanisms and causes of wear in dental enamel can reconstruct hominin diets (Lucas PW, Omar R et al 2013). Analysis of radiographs of fossil dentitions provides insights into the state of dental occlusion at death and possible dietary regimen practised (Sperber 2017). Dental caries can be used as a "foodprint" to identify dietary intakes of cariogenic foodstuffs.…”
Section: Dental Microwearmentioning
confidence: 99%